Laboratory evaluation of Isaria fumosorosea against Spodoptera littoralis - Zemek, R; Hussein, H M; Prenerová, E (Communications in agricultural and applied biological sciences, 2012)
Isaria fumosorosea (syn. Paecilomyces fumosoroseus) is potentially useful for the biological control of economically important agricultural and forest insect pests. We evaluated efficacy of two strains of this entomopathogenic fungus against last instar larvae and pupae of Egyptian cotton leafworm, Spodoptera littoralis. The first strain was Apopka 97 which is an active ingredient of commercial biopesticide PreFeRal WG (Biobest, Belgium). The second strain was isolated from Cameraria ohridella and is currently deposited under number CCM 8367 as a patent culture in the Czech Collection of Microorganisms in Brno. Blastospores of both strains were obtained after 120 hours submerged cultivation in grow media using orbital shaker. The concentration of blastospores was adjusted to 5 x 10(7) spores/ml of suspension. Soaking agent Tween 80 was added to the suspension at concentration 0.02%. Lethal effects of both fungal strains on S. littoralis were evaluated using standard dip test. Treated insects were individually placed into plastic Petri dishes (diam. 9 cm) and kept at constant laboratory conditions (temperature 23 degrees C, R.H. approx. 100%, 16L:8D photoperiod). Virulence of the strains was expressed as percentages of cumulative daily mortality corrected for mortality in the control variant. Obtained results revealed higher virulence of CCM 8367 blastospores to the last instar larvae of S. littoralis (93.1% mortality) on the 7th day after the treatment compared to Apopka 97 (65.5% mortality). Even more obvious difference was found in pupae, where corrected mortality of CCM 8367-treated pupae was 80.0% while mortality in Apopka 97-treated pupae reached only 3.3% on the 8th day after the treatment. We can conclude that the strain I. fumosorosea CCM 8367 has strong insecticidal effects on S. littoralis and has a potential to be implemented as a novel biocontrol agent.
Keywords: larva; Pupa; Pest Control, Biological; Spodoptera; Animals; Virulence; biologická kontrola škůdců; kukla; Time Factors; Paecilomyces; Hypocreales; časové faktory; virulence; Larva; zvířata